End-user computing, development, and software engineering new challenges - Dwivedi, Ashish N.; Clarke, Steve, 1950-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2012)
"This book explores the implementation of organizational and end user computing initiatives and provides foundational research to further the understanding of this discipline and its related fields"--Provided by publisher.
End-user computing : innovations and new understanding -- Contrasting it capability and organizational types : implications for firm performance / Byrd and Byrd -- Utilization and perceived benefit for diverse users of communities of practice in a healthcare organization / Walczak and -- Culturally compatible usability work: an interpretive case study on the relationship between usability work and its cultural context in software product development organizations / Livari -- Studying the documentation of an api for enterprise service-oriented architecture / Myers, Jeong, Xie, Beaton, Stylos, Ehret, Karstens, Efeoglu and Busse -- Mutual development : the software engineering context of end-user development / March and Andersen -- Approaches, frameworks, and techniques for end-user computing -- Woad : a framework to enable the end-user development of coordination-oriented functionalities / Cabitza and Simone -- Self-determined adoption of an ict system in a work organization / Korpelainen, Vartiainen and Kira -- A model of system re-configurability and pedagogical usability in an e-learning context : a faculty perspective / Wang, Doll and Deng -- End-user software engineering and why it matters / Burnett -- End user development and meta-design : foundations for cultures of participation / Fischer -- Investigating technology commitment in instant messaging application users / Wang and Datta -- End-user computing : evidence from practice -- Appropriation infrastructure : mediating appropriation and production work / Stevens, Pipek and Wulf -- Entering the clubhouse : case studies of young programmers joining the online scratch communities / Kafai, Fields, and Burke -- Enterprise systems training strategies : knowledge levels and user understanding / Coulson, Olfman, Ryan -- The influence of perceived source credibility on end user attitudes and intentions to comply with recommended it actions / Johnston and Warkentin -- Organizing end-user training : a case study of an e-bank and its elderly customers / Oinas-Kukkonen, Hohtari and Pekkola -- A path analysis of the impact of application-specific perceptions of computer self-efficacy and anxiety on technology acceptance / Hasan and Ahmed.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed January 23, 2012).
Keywords: End-user computing; Software engineering; Communities of practice; Computer self-efficacy and technology acceptance; E-learning; End user attitudes; End user development; End user software engineering; End user training; Enterprise systems training; ICT system adoption; IT capability; Organizational types; Electronic books